Successful treatment of cardiac dysfunction due to left main trunk obstruction and severe acute aortic regurgitation secondary to acute type A aortic dissection using Impella: a case report - Ai Sakai; Kenji Iino; Hideyasu Ueda; Yoshitaka Yamamoto; Hirofumi Takemura (Journal of Cardiothoracic Surgery)
Abstract Background Acute type A aortic dissection (A-AAD) with severe acute aortic regurgitation (AR) and coronary involvement is a potentially fatal condition that causes left ventricular volume overload and catastrophic acute myocardial infarction. We present the successful management of a patient using Impella 5.5 following cardiopulmonary arrest caused by A-AAD with severe acute AR and left main trunk (LMT) obstruction. Case presentation A 50-year-old man presented with acute anterior chest pain. The patient subsequently experienced a cardiac arrest, and veno-arterial extracorporeal membrane oxygenation (VA-ECMO) was administered accordingly. Contrast-enhanced computed tomography indicated type A aortic dissection extending from the sinotubular junction to the left common iliac artery. Transthoracic echocardiography revealed inversion of the aortic flap into the left ventricular outflow tract, resulting in acute severe AR and LMT obstruction. Based on these findings, the patient was diagnosed with A-AAD accompanied by severe acute AR and LMT obstruction. Emergent total arch replacement with a frozen elephant trunk (FET) was performed. However, the patient could not be weaned from cardiopulmonary bypass owing to cardiogenic shock, necessitating the introduction of VA-ECMO. Pulmonary capillary wedge pressure remained high at 22 mmHg. Subsequently, Impella 5.5 was introduced via a branch of the vascular graft to address the extensive myocardial damage due to preoperative LMT obstruction, acute AR-induced left ventricular volume overload, and increased afterload from VA-ECMO. The patient’s cardiac function gradually improved. VA-ECMO and Impella 5.5 were weaned on postoperative day 8 and 20, respectively. However, three months postoperatively, a MitraClip was used to progress secondary mitral regurgitation associated with left ventricular remodeling after myocardial infarction. The patient gradually recovered from the neurological deficit and was transferred for physical rehabilitation five months postoperatively. Conclusions The patient exhibited severe cardiac dysfunction due to extensive myocardial infarction and acute AR from A-AAD. Retrograde perfusion via VA-ECMO was required for systemic organ perfusion but was expected to hinder cardiac recovery. This report demonstrates that Impella effectively aids the restoration of cardiac function in such desperate conditions.